Analisis Keterampilan Berbicara melalui Proyek Penguatan Profil Pelajar Pancasila di SMK PERTIWI - Nurhasan; Mualimah, Siti; Sudrajat, Yayan (SINAU: Jurnal Ilmiah Pendidikan Dan Pembelajaran, 2023)
The problems in this study are as follows: (1) How are the speaking skills of Class X Students at SMK PERTIWI (2) What are the Factors Affecting Speaking Skills at SMK PERTIWI?, (3) What is the Solution to Improve Speaking Skills SMK PERTIWI. This type of research is descriptive qualitative research. Data collection techniques in this study used observation, interviews, and documentation techniques. The validity of the data used triangulation techniques, namely data reduction, data presentation, conclusion drawing and verification. The subjects selected were class X with a total of 20 students. The results of this study can be concluded: (1) The speaking skills of class X students of SMK PERTIWI are very good from 28.7% to 84.6%, (2) The factors that influence students' speaking skills are internal factors including factors from themselves and students' family backgrounds while external factors include community and school environmental factors, (3) solutions to improve students' speaking skills, namely: using interesting learning media, applying speaking practice methods, providing motivation to speak to students, and familiarizing students in discussing group. Through the research entitled "Analysis of Speaking Skills Through the Project for Strengthening the Profile of Pancasila Students at SMK PERTIWI" generally classified as very good.